Mimicking Enzymes: Taking Advantage of the Substrate-Recognition Properties of Metalloporphyrins in Supramolecular Catalysis - Abuhafez, Naba; Perennes, Antoine; Gramage-Doria, Rafael (Synthesis, 2022)
The present review describes the most relevant advances dealing with supramolecular catalysis in which metalloporphyrins are employed as substrate-recognition sites in the second coordination sphere of the catalyst. The kinetically labile interaction between metalloporphyrins (typically, those derived from zinc) and nitrogen- or oxygen-containing substrates is energetically comparable to the non-covalent interactions (i.e., hydrogen bonding) found in enzymes enabling substrate preorganization. Much inspired from host–guest phenomena, the catalytic systems described in this account display unique activities, selectivities and action modes that are difficult to reach by applying purely covalent strategies.
Keywords: porphyrins; supramolecular chemistry; homogeneous catalysis; pyridines; transition metals; Diels–Alder reaction